Fostering StudentsDigital Literacy In The Age Of The Internet In The Pandemic Era - Probowati, Yeni (KnE Social Sciences, 2023)
Being digitally literate is an ongoing process in which students must consistently keep up by actively learning and trying out new technology tools and resources, building skills with these technologies, and most importantly using this technology to meet their needs and achieve their goals. This paper considers how students can respond to digital media literacy in the internet era. It begins by exploring digital literacy and digital media literacy more specifically. Then, it approaches how digital media should be selected according to students characteristics, authenticity, appropriacy and sufficiency and then emphasizes the importance of the internet and it wide ranging utility. It argues that the advantages of digital technology give valuable contribution for the students. The paper aims to explore extensive use of potential digital media to empower the students, enlarge their knowledge, enhance their communication skills and enjoy better living condition and elevated status in society. The article concludes that digital literacy should be seen as part of global education in era of internet and the use of digital media properly. Keywords: Digital literacy; internet; pandemic era; digital media